Free-piston Stirling cryocooler (FPSC) for low-temperature applications down to 110 K. (September 2020) - Park, Jiho; Kim, Hyobong; Ko, Junseok; In, Sehwan; Hong, Yongju; Yeom, Hankil; Park, Seongje
Highlights: Development of free-piston Stirling cryocooler (FPSC) with linear compressor. Demonstration that the FPSC absorbs 1.03 kW heat at 110 K cold-end temperature . Demonstration that the oil-free compressor works with 0.75 compression efficiency. Verification of the numerical model with 10% deviation under various temperatures. Demonstration that the small-scale liquefier works with natural gas analogue fluid. Abstract: This research paper describes the experiments and demonstrations of the free-piston Stirling cryocooler (FPSC) we developed. Driven with an oil-free linear compressor, the FPSC is thoroughly tested with various cold-end temperatures between 110 K and 190 K, absorbing 1.03 kW heat at cold-end temperature of 110 K with electric input of 8 kW. The resulting cooler efficiency is estimated to be 0.13 considering a compression efficiency of 0.75. The experimental results are analyzed with a pre-developed numerical model that considers not only the thermodynamics of the working fluid of the FPSC but also the mechanical behavior of the reciprocating piston and displacer by introducing a fictitious damping coefficient to the equation of motion. The numerical model is able to predict the physical variables of the FPSC within 10% deviation under various cold-end temperature conditions. Thanks to the flexibility in regulating its cold-end temperature, the FPSC can be utilized for various applications, i.e., liquefied natural gas (LNG), semiconductor etching, bio/reagent preservation applications, etc. Finally, the FPSC is integrated as a major part of a small-scale liquefier to demonstrate the feasibility of liquefaction of natural gas (NG).